2010
DOI: 10.1002/jbm.b.31657
|View full text |Cite
|
Sign up to set email alerts
|

Improving the resistance to sliding contact damage of zirconia using elastic gradients

Abstract: Zirconia-based ceramics with high strength have been identified as a material of choice for sliding components in a variety of biomedical and engineering applications. Despite the high flexural strength, zirconia prostheses are still vulnerable to wear and surface damage. We hypothesize that such tribological damage may be substantially mitigated by an engineered grading of elastic modulus at the ceramic surface. In this study, graded structures were fabricated by infiltrating glass into the top and bottom sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…This can be achieved through graded structures, gradually changing the material composition across the core veneer interface and the core intaglio surface. In one set of studies (Zhang and Kim, 2009;Zhang and Ma, 2009;Kim et al, 2010b), zirconia was infiltrated with a silicate glass with a matched coefficient of thermal expansion. The percentage of glass changed from 100% to none across a 120-µm interphase.…”
Section: Graded Structures -Innovations For Damage Tolerancementioning
confidence: 99%
“…This can be achieved through graded structures, gradually changing the material composition across the core veneer interface and the core intaglio surface. In one set of studies (Zhang and Kim, 2009;Zhang and Ma, 2009;Kim et al, 2010b), zirconia was infiltrated with a silicate glass with a matched coefficient of thermal expansion. The percentage of glass changed from 100% to none across a 120-µm interphase.…”
Section: Graded Structures -Innovations For Damage Tolerancementioning
confidence: 99%
“…The bio-inspired design concept has been recently introduced to the development of new all-ceramic materials. The synthetic functionally graded material (FGM) architectures have been proved to significantly reduce stress concentration at the interface and toughen all-ceramic restorations [2][3][4][5][6][7] . The synthetic procedure involves pre-sintering zirconia core and glass infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Within this functionally graded layer, stress concentration is significantly reduced by virtue of the gradually changing elastic modulus [6][7][8][9] . Inspired by DEJ, some researchers introduced the concept of a bio-inspired, functionally graded material layer structure between the ceramic core and cement to reduce stress [10][11][12][13][14][15] . Huang et al 10) developed a two-dimensional all-ceramic restoration model with a bio-inspired functionally graded material (FGM) layer between the ceramic core and cement.…”
Section: Discussionmentioning
confidence: 99%
“…By using a rate-dependent slow crack growth (RDEASCG) model, critical loads were significantly improved and subsurface stresses that might induce cracks in the ceramic layer were reduced 11) . Numerous studies have also shown that functionally graded structure fabricated by infiltrating glass into the ceramic core exhibited higher load-bearing capacity through finite element analyses and contact loading experiments [12][13][14][15] . However, few studies focused on the explicit optimal design of bio-inspired functionally graded material layer (variation of gradients in elastic modulus in FGM), which might minimize tensile stress between the ceramic core and cement and uniformly distribute stress in FGM.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation